Risk Factors of Ureteral Stenosis After Percutaneous Microwave Ablation of Renal Tumor, a Single-Center Experience - Wu, Jiapeng; Yu, Jie; Cheng, Zhigang; Han, Zhiyu; Yu, Xiaoling; Li, Kai; Hu, Ping; Liu, Fangyi; Liang, Ping (Frontiers in Oncology, 2020)
Background： Ureteral stenosis after percutaneous microwave ablation of renal tumor is a rare but severe complication, and the risk factors of it is not apparent. Purpose: This study aimed to investigate the risk factors for stenosis of ureter after microwave ablation treatment of the renal tumor that is a rare complication. Material and Methods Two hundred eleven patients underwent microwave ablation for the treatment of renal tumor were retrospectively analyzed from September 2006 to August 2019. Demographic characteristics, clinical features, ablation parameters, and outcomes were analyzed to find out the potential risk factors of this complication. P < 0.05 is considered significant. Results Six of 211 patients developed ureter stenosis, and the rate of this complication is 2.84%. The median time of emerge of hydronephrosis was 226 (range 3-390) days. Univariate analysis shows the distance between ureter and tumor(P=0.225) or ablation zone(P=0.089) is not related to this complication. Post-operative urine routine (RBC, P=0.001; WBC, P=0.035) and R.E.N.A.L score (P < 0.001) is related to this complication. But after multivariate logistic analysis, only R.E.N.A.L score(P=0.004) is associated to this complication. The location and growth pattern of tumor, the energy of ablation, were not related to this complication independently. Conclusion: The stenosis of the ureter after MWA of renal tumor is not associated with the tumor size, location, or the distance between the ureter and tumor and ablation site independently. But R.E.N.A.L score is associated to ureter stenosis after microwave ablation for the treatment of renal tumor, which combines the information of location, depth and size of tumor. Pre-operative evaluation of the tumor is necessary for avoiding ureter stenosis. Further studies should focus on these risk factors of this complication.